A comparative study of the impact of focused vs. comprehensive corrective feedback and revision on ESL learners' writing accuracy and quality. (September 2021) - Rahimi, Mohammad
The impetus for the present study came from Ferris' (2010) article discussing the gap between theory, research, and practice in written corrective feedback (WCF). To address this gap, the present study aimed at comparing the impact of focused vs. comprehensive WCF and revision on the improvement of written accuracy of learners of English as a second language (ESL), with a focus on their global linguistic errors (sentence and word); the study also examined how this improvement contributed to the students' writing quality, defined in terms of clarity of expression and text comprehensibility. Data was collected from 78 intermediate French ESL learners randomly assigned to four different treatment groups: two groups received focused WCF and two groups comprehensive WCF; one of the focused and one of the comprehensive groups were required to revise their writing and the other two groups did no revision after WCF. A comparison was made between the error means of the four groups on three out of seven essays they wrote during a 15-week writing course: week one (T1), week eight (T2) and week 14 (T3). The results revealed that the focused groups were more successful than the comprehensive ones in reducing their words errors at T2; no significant effect was observed for revision. Also, the focused-revision group outperformed the other groups at both T2 and T3 in reducing their sentence errors. The comprehensive-revision, however, group was more successful than the other groups in improving their overall written accuracy. The results also showed that the focused-revision group made more improvement than the other three groups in their writing quality at T3.